Comparative Literature. Issues and Methods / La Littérature comparée. Questions et méthodes. Editor: Lisa Block de Behar, Montevideo, 2000, σελ. 272. - Ταμπάκη Άννα (Σύγκριση/Comparaison/Comparison, 2017)
Δεν διατίθεται περίληψη.